Search for a resonance decaying into WZ boson Pairs in pp̄ collisions - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2010)
We present the first search for an electrically charged resonance W′ decaying to a WZ boson pair using 4.1fb-1 of integrated luminosity collected with the D0 detector at the Fermilab Tevatron pp̄ collider. The WZ pairs are reconstructed through their decays into three charged leptons (≤=e, μ). A total of 9 data events is observed in good agreement with the background prediction. We set 95% C.L. limits on the W′WZ coupling and on the W′ production cross section multiplied by the branching fractions. We also exclude W′ masses between 188 and 520 GeV within a simple extension of the standard model and set the most restrictive limits to date on low-scale technicolor models. © 2010 The American Physical Society.
Keywords: Background prediction; Branching fractions; Charged leptons; Collider; Fermilab Tevatron; Integrated luminosity; Production cross section; The standard model; Resonance; Bosons